2008
DOI: 10.1002/chir.20550
|View full text |Cite
|
Sign up to set email alerts
|

Guest‐dependent conformation of 18‐crown‐6 tetracarboxylic acid: Relation to chiral separation of racemic amino acids

Abstract: (+)-18-crown-6 tetracarboxylic acid (18C6H(4)) has been used as a chiral selector for various amines and amino acids. To further clarify the structural scaffold of 18C6H(4) for chiral separation, single crystal X-ray analysis of its glycine(+) (1), H3O+ (2), H5O2+ (3), NH4+ (4), and 2CH3NH3+ (5) complexes was performed and the guest-dependent conformation of 18C6H(4) was investigated. The crown ether ring of 18C6H4 in 3, 4, and 5 took a symmetrical C2 or C2-like conformation, whereas that in 1 and 2 took an as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 33 publications
3
28
0
Order By: Relevance
“…Alternatively, the interconversion barriers between conformer 2 and conformer 1 might be sufficiently high as to induce kinetic trapping of the higher energy conformer 2 under the present experimental conditions. 13 This would result in a non-equilibrium distribution favouring a population of conformer 2 higher than expected from energetics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the interconversion barriers between conformer 2 and conformer 1 might be sufficiently high as to induce kinetic trapping of the higher energy conformer 2 under the present experimental conditions. 13 This would result in a non-equilibrium distribution favouring a population of conformer 2 higher than expected from energetics.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies with x-ray crystallography and nuclear magnetic resonance spectroscopy have demonstrated the affinity of 18c6H 4 for protonated amines, amino acids, amino alcohols and further compounds with free amino functionality. [8][9][10][11][12][13][14][15][16] Those studies have provided evidence for the relevance of the barrel-like and bowl-like structures adopted by 18c6H 4 . Such structures are sustained by intramolecular H-bonding involving the carboxyl groups and by intermolecular interactions of the cationic guest with the ether and carboxyl oxygen atoms.…”
Section: Introductionmentioning
confidence: 86%
“…Analyte complexation is due to the formation of hydrogen bonds between the protonated amine and the oxygen atoms of the macrocycle. From a series of X-ray analyses employing amino acids as guest molecules Nagata and colleagues concluded that (+)-18C6H4 adopts an asymmetric C1-type conformation forming a bowl like shape [55][56][57]. The N-H and C α protons of the amino acid guest molecule interact with the oxygen atoms of the macrocycle and with the carboxylate groups of the side chains.…”
Section: Chiral Separations Mechanisms In Capillary Electrophoresismentioning
confidence: 97%
“…Finally, dipeptides containing branched groups were better resolved than those with straight-chain alkyl groups [81]. Recent studies [82,83] also pointed out the conformational changes that occur when (+)-18C6H 4 interacts with an amino acid [82] or with positively charged species such as glycine + , H 3 O + , H 5 O 2 + , NH 4 + , and 2CH 3 NH 3 + [83]. When interacting with amino acids, the planar/symmetric ring conformation of the selector changes into a convex/asymmetric one.…”
Section: Crown Ethers As Chiral Selectorsmentioning
confidence: 99%